Factors Affecting Livelihood Security of the Tribal Women in Crop Based Livelihood Activities - Dagar, Asha; Upadhyay, Rajshree (Indian Journal of Extension Education, 2022)
The study was aimed to find out the factors affecting by tribal women and association of different factors with livelihood security of the tribal women in crop based livelihood activities conducted in three districts of Rajasthan namely Dungarpur, Udaipur and Banswara 180 respondents data were collected through a well- structured interview schedule. Majority of the respondents had occasional access to extension agency, mass media sources, technological information as well print media. More than half of the respondents never had access to regular income, less than half of the respondents sometimes only produced new products, used improved methods and practices and took loan for carrying out livelihood. The livelihood security of the respondents was associated with access to resources, access to technological information, market and regular income, risk factors, risk taking ability and decision making ability. It can be inferred that all these factors affected to livelihood security of the tribal families with crop based livelihood.